Generation and characterization of a high-affinity monoclonal antibody for MUC1 measurement in breast cancer - Cheah, S.H.; Hamid, S.S.A. (Mary Ann Liebert, Inc., 2011)
Breast mucin is secreted by breast tumor cells and serves as a marker for breast cancer. Thus, antibodies against breast mucin will be valuable in the development of immunotherapy and laboratory diagnostic tests. Monoclonal antibodies (MAbs) against breast cancer–associated antigen were generated and characterized. Balb/c mice were immunized with breast cancer-associated antigen CA15-3, and subsequently splenocytes from immunized mice were fused with myeloma cells. After fusion, culture supernatants from hybridomas surviving HAT medium were screened by enzyme-linked immunosorbent assay (ELISA). A total of eight hybridomas producing MAbs against breast cancer showed significant levels of antibody activity against CA15-3. Two selected stable hybridomas were adapted into CELLine CL 350 bioreactors, and the MAbs produced were characterized for their subclass, specificity, and affinity. The MAbs were of high specificity and affinity as shown by ELISA. The MAbs produced may represent a powerful tool and are considered promising reagents for use in diagnosis and detection of early stage of the disease.